2017
DOI: 10.1523/jneurosci.1174-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

FGF-FGFR Mediates the Activity-Dependent Dendritogenesis of Layer IV Neurons during Barrel Formation

Abstract: Fibroblast growth factors (FGFs) and FGF receptors (FGFRs) are known for their potent effects on cell proliferation/differentiation and cortical patterning in the developing brain. However, little is known regarding the roles of FGFs/FGFRs in cortical circuit formation. Here we show that //3 and /// mRNAs are expressed in the developing primary somatosensory (S1) barrel cortex. Barrel cortex layer IV spiny stellate cells (bSCs) are the primary recipients of ascending sensory information via thalamocortical axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Previous studies also showed that genetic destruction of the FGF22 signal not only reduces the number of new axons formed in the injured loci but also changes the molecular organization of the forming axons (Terauchi et al, 2010). Therefore, treatment of injured spinal cord with FGF22 can effectively promote axonal regeneration and functional recovery (Huang et al, 2017). The experimental results showed that apoptosis signaling molecules in the FGF22 treatment group were inhibited, which indicated that FGF22 can effectively inhibit endoplasmic reticulum stress, reduce neuronal apoptosis and play a crucial role in neuronal protection.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies also showed that genetic destruction of the FGF22 signal not only reduces the number of new axons formed in the injured loci but also changes the molecular organization of the forming axons (Terauchi et al, 2010). Therefore, treatment of injured spinal cord with FGF22 can effectively promote axonal regeneration and functional recovery (Huang et al, 2017). The experimental results showed that apoptosis signaling molecules in the FGF22 treatment group were inhibited, which indicated that FGF22 can effectively inhibit endoplasmic reticulum stress, reduce neuronal apoptosis and play a crucial role in neuronal protection.…”
Section: Discussionmentioning
confidence: 98%
“…For example, FGF1 was reported to stimulate neurite outgrowth in PC12 cells through activating FGF receptor 1 (FGFR1) and FGF receptor 3 (FGFR3), with the latter having more potency [33]. Gain of functions for FGF9 and FGF10 has been shown in extensive dendritogenesis in the developing primary somatosensory (S1) barrel cortex [10].…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factors (FGFs) influence neuronal morphology [8][9][10] and are involved in the pathogenesis of many neurodegenerative diseases [11][12][13]. Fibroblast growth factor 9 (FGF9), a specific type of FGF, has been reported to regulate neuronal development in vivo [10] and also has been suggested to provide neuroprotective functions in Parkinson's disease (PD) and Huntington's disease (HD), two important neurodegenerative diseases [13][14][15][16]. This suggests that FGF9 may be an exogenous candidate to intervene in these diseases through regulating neuronal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…However, X-ray structural analysis of the FGF ligand-binding region reveals that D3 is folded into a stable immunoglobulin-like structure [ 28 ]. The FGF-FGFR complexes regulate cell proliferation, differentiation, and migration through complicated signal transduction pathways in various tissues [ 29 , 30 , 31 , 32 ]. The relationships of FGF receptors and FGF ligands are shown in Figure 3 .…”
Section: Fgfs and Their Receptorsmentioning
confidence: 99%